Cervico-Vaginal Smears—Cytologic Examination - Horton, Robert (1966)
Discrepancies among classification systems of Papanicolaou smears and lack of communication between cytologist and clinician are not uncommon. An attempt should be made by the cytologist to estimate, on a percentage scale, the likelihood of any given smear indicating carcinoma. This enables a more realistic and systematic management of a patient whose smear is other than negative. Proper technique in obtaining the smear is essential to proper interpretation, and it must be stressed that a negative smear in a patient with a cervical lesion does not rule out carcinoma. Likewise, a negative smear cannot rule out carcinoma higher in the generative tract.